Governance in developing Asia public service delivery and empowerment - Deolalikar, Anil B.; Jha, Shikha; Quising, Pilipinas F. (Cheltenham, UK Edward Elgar Publishing, 2015)
Governance in Developing Asia is one of the first books of its kind to provide an overview of the role that better governance and citizen empowerment can play in improving public service delivery in developing Asia. The World Development Report 2004 set a framework for public service delivery in terms of the short and long roads to accountability of service providers to citizens. More than a decade on, this important book revisits the issue and departs from the WDR framework, highlighting its shortcomings and offering alternative solutions.
1. Overview -- 2. Governance in developing Asia: concepts, measurements, determinants and a paradox -- 3. Do governance indicators explain growth performance? A cross-country analysis -- 4. Governance and development outcomes in Asia -- 5. Corruption in Asia and the Pacific: a manifestation of weak governance -- 6. The state of public services in developing Asia -- 7. Harnessing public-private service delivery arrangements in developing Asia -- 8. Improving service delivery through decentralization -- 9. Improving education services: district governance and student learning in Indonesia -- 10. Citizen empowerment in service delivery -- 11. Rights, accountability and citizenship: India's emerging welfare state -- 12. Using ICT to improve governance and service delivery to the poor -- 13. Concluding remarks.
Co-publications of the Asian Development Bank and Edward Elgar Publishing.
Keywords: Public administration -- Asia; Public administration -- Developing countries; Civil service -- Asia; Civil service -- Developing countries